Estudo do comportamento eletromecânico de músculos artificiais baseados em compósitos de polímero ionomérico e metal por meio da análise de vídeo - Saccardo, Matheus Colovati (2020)
Ionomeric polymer-metal composites (IPMCs) are smart materials, which have a metal/polymer/metal sandwich-like structure and are capable to deform in response to electrical stimuli and vice versa. In addition, they have low density, flexibility, biocompatibility and low drive voltage. Therefore, they are promising materials for a wide range of applications, such as actuators, sensors, and as artificial muscles. The operating mechanism of these devices consists of the migration of hydrated ions within the polymer's ionomeric channels in response to an electric field generated after the application of a bias between metal electrodes. For this reason, its electromechanical performance depends on several factors, such as electrical stimulus, hydration level of the polymeric membrane and counterions. Therefore, in this work, traditional (electrical, morphological and deformational) and complementary techniques (SEM, TGA and EIS) were used to characterize artificial muscles under different conditions of electrical stimulus (1 to 5 V), relative humidity (30% at 90%) and containing counter ions of varying sizes (H+, Li+, Na+ and K+) and distinct chemical characteristics (1-butyl-3-methylimidazole - BMIM+), in order to elucidate and understand their electromechanical behavior. Also, a method of video analysis was also used in conjunction with a video analysis and modeling tool built on the Java Open Source Physics (OSP) framework, allowing for a more accurate electromechanical behavior analysis. Results showed that the electromechanical behaviour, electric charge storage, and the Coulombic Efficiency of the devices increased with the reduction of counterion ionic radius and increase of the hydration level of the polymeric matrix. The mechanical performance decreased with the number of cycles, showing a limited life cycle for the device. The image analysis proved to be efficient, effective and low-cost technique.